Bandwagon of suspicion : Investigating credibility perceptions toward relayed information on WhatsApp - Hamka Afiq Mohamed (Nanyang Technological University, 2020)
This study conceptualizes the electronically-relayed-information cue (ERIC), which indicates if a piece of content has been passed on via electronic means, and if so, how many times. Situating ERICs as agency cues under the MAIN model, this study explores how the presence of “Forwarded” labels on WhatsApp affects perceptions of message credibility. It also considers if this effect depends on message congruence and users’ knowledge of the cues’ meaning. This study features a 3 (within-subjects: no ERIC vs. weak ERIC vs. strong ERIC) × 2 (between-subjects: congruent vs. incongruent) × 2 (between-subjects: informed vs. uninformed) experiment conducted on a Singapore sample (N = 266). The results show that messages with weak ERICs were perceived as less credible than messages without ERICs. A three-way interaction was observed where users who saw congruent messages, and were not informed about the meanings of ERICs, perceived messages with either ERIC as less credible than messages without ERICs. The results imply that in certain contexts, ERICs can induce suspicion toward the relayed content. This is consistent with WhatsApp’s rationale for introducing the “Forwarded” labels. This study contributes to a more holistic understanding of message effects that parses the element of relay in mediated communication.